Manajemen Badan Amil Zakat (BAZNAS) Kabupaten Ciamis dalam Meningkatkan Ekonomi Mustahik - Fazriati, Rani Nurisa; Saepuloh, Uwoh; Setiawn, Asep Iwan (Tadbir: Jurnal Manajemen Dakwah, 2021)
This study aims to determine the planning, organization, implementation and supervision carried out by the National Amil Zakat Agency (BANZAS) of Ciamis Regency in improving the mustahik economy. The method used in this research is descriptive qualitative method. Data collection techniques through observation, interviews, documentation. The results of this research show that the planning carried out in improving the mustahik economy is carried out well, structured and systematic. Organizing consists of making a predetermined organizational structure along with its duties and authorities, implementation is carried out by realizing the planned program. Supervision uses two methods, namely direct supervision and indirect supervision, with the aim of seeing and supervising mustahik in the development of the business they run.